Penyuluhan Pemasaran Produk Umkm dan Literasi Keuangan Bagi UMKM dan Masyarakat Di RW 012 Desa Mangunjaya Kecamatan Tambun - Tri Kunawangsih Purnamaningrum; Masfar Gazali; Maria Ariesta Utha; Ali Gesang Widodo (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
The Community Service Program takes the theme Product marketing counseling for MSMEs, as well as Investment Household Financial Literacy. The PKM participants are community members consisting of housewives and Youth Organizations who live in Mangunjaya Village, South Tambun, Bekasi. The purpose of this PKM activity is to provide counseling on how to increase the ability to market products as well as counseling on how to manage finances so that they can develop business and investment so that people's welfare can be improved. The expected output is in the form of increasing public knowledge about how to become entrepreneurs and having skills in managing personal finances and managing MSME finances.